Gold(I) Complexes of N-Heterocyclic Carbene Ligands Containing Benzimidazole: Synthesis and Antimicrobial Activity - İlknur Özdemir; Nazan Temelli; Selami Günal; Serpil Demir (Molecules, 2010)
Gold(I) N-heterocyclic carbene (NHC) complexes were obtained in good yields from the corresponding silver complexes by treatment with [AuCl(PPh3)] following the commonly used silver carbene transfer route. The silver complexes were synthesized from the benzimidazolium halide salts by the in situ reactions with Ag2O in dichloromethane as a solvent at room temperature. All gold complexes have been characterized by 1H-NMR, 13C-NMR and IR spectroscopy and elemental analysis. Au-NHC complexes were evaluated for their in vitro antimicrobial activity against a variety of Gram-positive and Gram-negative bacteria and fungal species.